Pricing weather derivatives in Keflavík Airport - Friðrik Sveinsson 1995- (2021)
Climate change is an increasing threat to the human population. The increasing threat of extreme weather conditions forces companies to look at their weather-related risks and how companies can protect themselves financially against these types of risks. The purpose of this thesis is to examine how to model two types of weather derivatives in Keflavík Airport: temperature derivative and wind derivative. Temperature derivatives are known commodities and are actively traded in the CME market, but there is not an active market for wind derivatives. Wind derivatives have been traded in recent years over the counter. We will go through the modelling approach, the forecast and the simulation of both the temperature and the wind speed in Keflavík Airport. We price a temperature derivative with three different strike prices using the Monte Carlo simulation. Then we look at the company Icelandair and price a wind derivative specially fitted to their needs. We price the derivative using the Monte Carlo simulation for 4 different indices: first, the Nordix Speed Index, which is well known in weather derivative theory, and then we create three new contracts based on the call and put option pricing formulas. In conclusion, Icelandic financial institutions should seriously consider selling weather derivatives in Iceland, although the modelling approach is quite difficult and the strike price needs thorough correlation analysis between the weather and the companies’ costs. Icelandic companies could benefit greatly on pricing weather-related risk and fluctuate the cost of the contract into their prices. Fyrirtækjum stafar aukin áhætta gagnvart loftslagsbreytingum. Slæm veðurskilyrði neyða fyrirtæki til þess að skoða veðurtengda áhættur og hvernig þau geta verndað sig fjárhagslega gegn veðurtengdum áhættum. Tilgangur þessarar ritgerðar er að skoða hvernig hægt er að verðleggja tvær tegundir af veðurafleiðum á Keflavíkurflugvelli. Hitastigs- og vind afleiður. Hitastigs afleiður eru þekkt fyrirbæri og eru stunduð virk viðskipti ...